2015
DOI: 10.1097/pep.0000000000000178
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Pediatric Balance Scale Using Rasch Analysis

Abstract: The PBS items are best targeted to preschool-age children; additional children with known balance dysfunction are required to fully assess functioning of the easiest PBS items. Revisions may improve PBS utility in older children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 18 publications
4
9
0
1
Order By: Relevance
“…Of the 14 PBS items, five items (item 8, 9, 10, 13, and 14) presented positive logit values, and nine items (item 1, 2, 3, 4, 5, 6, 7, 11, and 12) negative logit values. These findings are consistent with previous research and similar to developmental skill acquisitions in children 3 ) . In addition, of the 10 FAB scale items, only one (item 1) showed a negative logit value, and the rest showed positive logit values.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Of the 14 PBS items, five items (item 8, 9, 10, 13, and 14) presented positive logit values, and nine items (item 1, 2, 3, 4, 5, 6, 7, 11, and 12) negative logit values. These findings are consistent with previous research and similar to developmental skill acquisitions in children 3 ) . In addition, of the 10 FAB scale items, only one (item 1) showed a negative logit value, and the rest showed positive logit values.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, PBS has relatively easier items than the FBA scale. The lack of items assessing higher function is the primary weakness of the PBS; thus, the assessment of higher-functioning individuals is limited 3 ) . Furthermore, the PBS is not enough to distinguish the difference of function in children with cerebral palsy 11 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tasks that narrow down the base of support, such as items 7, 8, and 9, increase the sway in children with ASD. The psychometric study 24 revealed that 82%, 48%, and 48% obtained maximum performance in these tasks, respectively. Tasks 10 and 11 assess dynamic PB.…”
Section: Childmentioning
confidence: 92%
“…Mini BEStest, BEStest y fukuda test, estos se encargan de predecir riesgo de caída en pacientes con alteraciones neuromusculares, osteomusculares y vestibulares (Agrawal, 2011) (Benka Wallen, 2016) (Honaker, 2009) (Hong, 2015) (Munnings, 2015) (O'Hoski, 2015 (Saso, 2016) (Tsang, 2013) (Zhang, 2011). En población pediátrica se utiliza la escala Pediatric balance scale en pacientes con parálisis cerebral para la evaluación de las respuestas selectivas de balance en niños (Darr, 2015) (Lim, 2015).…”
Section: Balanceunclassified